[{AgL}2Mo8O26]n– complexes: a combined experimental and theoretical study. Issue 5 (13th January 2020) - Chupina, Anastasia V.; Shayapov, Vladimir; Novikov, Alexander S.; Volchek, Victoria V.; Benassi, Enrico; Abramov, Pavel A.; Sokolov, Maxim N.
Abstract : Two sets of silver–molybdate complexes with L = XR3 (X = P, As, Sb; R3 = Ph3, Ph2 Py) and functionalized pyridine-based ligands have been studied with different techniques. Abstract : Self-assembly reactions between AgNO3, L (PPh3, PPh2 Py, AsPh3, SbPh3 ) and [β-Mo8 O26 ] 4− in DMF led to the formation of [β-{AgL}2 Mo8 O26 ] 2− anions, which were isolated as Bu4 N + salts (1–4 ) and characterized by XRD, IR and elemental analysis. In the crystal structures Ag + can switch the coordination number from 5 (P, As) to 6 (Sb) by uptake of a DMF molecule. High-level QAIM analysis of the coordination sphere around Ag shows critical points even in the case of longer Ag–O distances. Changing the ligand type to a family of substituted pyridines results in novel Ag–L–POM complexes with different environments around Ag + . For 3-X-pyridine ligands (X = Cl, Br, I), complexes with additional DMF molecules [β-{AgL(DMF)}2 Mo8 O26 ] 2− (5–7 ) have been isolated. Halogen bonding of the X⋯O type was detected in the crystal structures of 5–7 and studied by DFT calculations, providing estimated energies from 0.9 to 3.4 kcal mol −1 . Variation of substituents at the pyridine ring results in the formation of [β-{AgL}2 Mo8 O26 ] 2− in the case of 2-NH2 -py (8 ), 2-CH3 -Py (9 ), 2, 4, 6-collidine (10 ) and 2, 6-NH2 -py (11 ). Solution behavior of 1–4 in CH3 CN was studied by a hyphenated HPLC–ICP-AES technique. According to the results, the [β-{AgL}2 Mo8 O26 ] 2− anions are largely dissociated in this medium. An attempt to change the [Mo8 O26 ] 4− precursor to [Mo6 O19 ] 2− (in the case of AgNO3 and PyPPh2 ) resulted in the crystallization of [Ag2 (PyPPh2 )2 (DMF)4 ][Mo6 O19 ] (12 ).